Hope in Hard Times : Norvelt and the Struggle for Community During the Great Depression - Kelly, Timothy, 1960-; Cary, Michael D., 1950-; Power, Margaret, 1953- (Book collections on Project MUSE., 2016)
"Explores the history of Norvelt, Pennsylvania, originally known as Westmoreland Homesteads, which was founded in 1934 as part of the New Deal homestead subsistence program"--Provided by publisher